How to foster scientists’ creativity - Park, Seungbae (Creativity Studies, 2016)
Scientific progress can be credited to creative scientists, who constantly ideate new theories and experiments. I explore how the three central positions in philosophy of science – scientific realism, scientific pessimism, and instrumentalism – are related to the practical issue of how scientists’ creativity can be fostered. I argue that realism encourages scientists to entertain new theories and experiments, pessimism discourages them from doing so, and instrumentalism falls in between realism and pessimism in terms of its effects on scientists’ creativity. Therefore, scientists should accept realism and reject both pessimism and instrumentalism for the sake of scientific creativity and progress.